The Status of Government Buildings Following the Relocation of the National Capital (IKN): A Normative Juridical Analysis - Erfina Yarly; Irwan Triadi (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study examines the legal implications of relocating Indonesia’s capital city from Jakarta to Nusantara, particularly concerning the status and management of State-Owned Assets (BMN) that have long supported the functions of the central government. Existing regulations, such as Law No. 1 of 2004 on State Treasury and Government Regulation No. 27 of 2014 on the Management of State/Regional Assets—were not designed to anticipate a full-scale relocation of the national government. As a result, a regulatory gap emerges regarding the future of government buildings that will be vacated in Jakarta. Employing a normative juridical research method with statutory, conceptual, and analytical approaches, supported by rechtsvinding (legal discovery), this study explores potential policy options for managing state assets after the relocation. Comparative insights from Canberra, Brasília, and Putrajaya reveal several possible models, ranging from repurposing and leasing schemes to cooperative utilization and selective asset sales. The findings highlight the urgency of establishing a specific Government Regulation in Lieu of Law (Perppu) to govern asset classification, utilization mechanisms, and accountability standards to ensure transparent and effective post-relocation asset management. The study recommends the formation of a National Task Force for BMN Repurposing, the adoption of an asset classification system (A–D), the strengthening of audit mechanisms, and the mandatory publication of utilization reports as a measure of public transparency.